The role of sonoelastography in the evaluation of hepatic fibrosis in pediatric patients - Bilgin, Erkan; Yaltırık Bilgin, Ezel; Özhan Oktar, Suna (Journal of Surgery and Medicine, 2021)
Background/Aim: Hepatic fibrosis is caused by excessive accumulation of collagen-containing extracellular matrix proteins in chronic liver diseases. The gold standard for determining the degree of liver fibrosis is liver biopsy, which is an invasive method with complication risks. This study aimed to evaluate the potential role of ultrasound elastography, a non-invasive method, in the assessment of hepatic fibrosis among pediatric patients. Methods: Twenty-four pediatric (0-18 years) patients with chronic liver disease and suspected hepatic fibrosis were included in this study. All patients were evaluated with B-mode and sonoelastography using Hitachi EUB 7500 digital ultrasound equipment. The biopsy procedure was performed on all patients a week after sonoelastography. Elastographic scores of liver parenchyma were categorized into four main groups, nonfibrotic, mild, moderate, and severe fibrosis. Strain index values were calculated. The elastographic scores and mean strain index values of the liver parenchyma were correlated with their pathological diagnosis. Results: Elastographic scores and strain index values were significant for the presence of hepatic fibrosis (P=0.001 and P=0.006 respectively). Elastography has 100% sensitivity and 83.3% specificity to distinguish hepatic fibrosis when the cut-off value of strain index is 1.03. Conclusion: Our findings support that real-time elastography is a non-invasive method for the diagnosis and staging of hepatic fibrosis with the potential to prevent recurrent biopsy and complications.